Plan de negocios para la creación de una agencia de viajes especializadas en ecoturismo, con operaciones en el Departamento del Magdalena y la Guajira - Lara Peralta, Michelle; Roldan Amaya, Nora (Universidad Antonio Nariño, 2022)
Through the analysis of tourism practices, it was possible to identify the current and future transcendences, from an economic, social, environmental aspect, which seeks to meet the needs of tourists, the environment and industry. In search of developing support standards focused on tourism aspects in general, including the environment, economic and social aspects, we have opted for the development of a business model oriented towards ecotourism. El Magdalena, noted for its incredible areas full of nature, make it a very popular destination, to the point of turning the city of Santa Marta into one of the best tourist destinations in Colombia. In fact, La Guajira becomes one of the experiences out of the ordinary, where there is perfect harmony between man and his environment, the diversity of the ecosystems makes this department unique in Colombia, allowing ecotourism to play an important role in the development and social change of the territories seeking to enhance the development of the region. For the present project, mixed research was carried out, the collection of qualitative and quantitative data was sought, which allowed us to identify with breadth and depth whether the ecotourism in Magdalena and La Guajira, it is a useful tool to preserve biodiversity and local culture, as well as the sustainability of the environment.